A STUDY OF BODY MASS INDEX IN THE POPULATION AND ITS ASSOCIATION WITH BLOOD PRESSURE AND SERUM LEVELS OF GLUCOSE AND TRIACYLGLYCEROL - SHARBARI BASU (International Journal of Pharma and Bio Sciences, 2013)
The prevalence of metabolic diseases in the urban and semi-urban population in India is high. Most people are unaware of the risks associated with obesity, diabetes mellitus, hypertension and dyslipidemia. This study was undertaken to find the association between Body Mass Index (BMI) and the fasting levels of blood glucose, triacylglycerol along with hypertension in the local population who were apparently healthy.One hundred and nine healthy people were segregated into four group based on BMI- Lean, Normal, Overweight and Obese. The mean values of fasting and post- prandial blood sugar and fasting triglyceride and the range of systolic and diastolic blood pressure was found to increase with the increase in BMI in the four groups. Fifteen cases were found to have Metabolic Syndrome.A close association of the risk factors for cardiovascular diseases with increasing BMI was found to exist in the population studied during a routine health check-up.